From cigarettes to compulsions: a longitudinal study in de novo Parkinson's disease - Massara, Matilde; Vedovelli, Luca; Masina, Fabio; M.J. Edelstyn, Nicky; Silvia Bisiacchi, Patrizia; Di Rosa, Elisa (Frontiers in Psychology, 2025)
IntroductionParkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease. Among the environmental and lifestyle factors associated with disease onset, cigarette smoking represents one of the most paradoxical. While substantial evidence has demonstrated a protective effect of smoking against the development of PD, smoking appears to worsen symptomatology, particularly by exacerbating impulsive-compulsive behaviors (ICBs) in people with PD (PwPD). However, longitudinal studies examining the effects of cigarette smoking on the progression of PD remain limited. Moreover, recent studies often involve mixed samples of treated and untreated PwPD, potentially confounding the impact of dopamine replacement therapy with that of smoking on ICBs.MethodsIn the present study, we investigated a cohort of de novo PwPD, tracking their motor, cognitive, affective, and behavioral outcomes over 5 years, to better clarify the role of smoking in disease progression. Data were obtained from the Parkinson's Progression Markers Initiative and included 166 PwPD (119 non-smokers and 47 former smokers) and 79 healthy controls (48 non-smokers and 31 former smokers).ResultsOur results revealed that a significantly higher percentage of former-smoker PwPD (28%) exhibited at least one ICB compared to non-smoker PwPD (13%; Pearson's 2(1) = 5.45, p = 0.02). No other significant differences between non-smokers and former smokers emerged in motor or non-motor symptoms, either in PwPD or in healthy individuals.DiscussionIn conclusion, the novelty of our findings lies in showing that smoking-related influences on impulsive-compulsive behaviors in PD are most evident at the de novo stage, before any dopaminergic treatment. This temporal specificity may help resolve previous inconsistencies in the literature and underscores the importance of distinguishing between environmental and pharmacological effects on symptom development.